2010
DOI: 10.1002/cncr.25201
|View full text |Cite
|
Sign up to set email alerts
|

The culture of faith and hope

Abstract: Purpose Patients’ estimates of their chances of therapeutic benefit from participation in early-phase trials greatly exceed historical data. Ethicists worry that this “therapeutic misestimation” undermines the validity of informed consent. Patients and Methods We interviewed 45 patients enrolled in phase I or II oncology trials about their expectations of therapeutic benefit and their reasons for those expectations. We employed a phenomenological, qualitative approach with one primary coder to identify emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
91
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(98 citation statements)
references
References 63 publications
6
91
1
Order By: Relevance
“…An alternative explanation is that this subset of patients, despite having been exposed to this information, have chosen to maintain unrealistic hope. The concept of therapeutic optimism has been reported before,8, 14, 17 and phase 1 physicians have to walk a fine line between reiterating a patient's poor prognosis, which may be seen as patronizing, and not disregarding the importance of human hope 10, 11, 14…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…An alternative explanation is that this subset of patients, despite having been exposed to this information, have chosen to maintain unrealistic hope. The concept of therapeutic optimism has been reported before,8, 14, 17 and phase 1 physicians have to walk a fine line between reiterating a patient's poor prognosis, which may be seen as patronizing, and not disregarding the importance of human hope 10, 11, 14…”
Section: Discussionmentioning
confidence: 98%
“…Research into patients' perceptions has generally focused on participants who have already enrolled or who are considering entry into early‐phase clinical trials, that is, after discussions have already taken place 8, 12, 13, 14, 15. Patients have demonstrated unrealistically high expectations of personal benefit or even a cure from these investigational agents 15, 16, 17.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some argue this hope is therapeutic and that it assists patients and their loved ones in coping with the emotional pain triggered by anticipating the final separation. Others take a bleaker, but more realistic, view, one that posits that talking only about anticancer treatment, instead of considering the big picture, distracts both the patient and the doctor from confronting their feelings of helplessness and grief and risks leaving patients and their loved ones unprepared for the final weeks or months [3][4][5][6][7][8]. In our essay, we reflect on our conversations with patients about therapeutic failure in the era of ever-expanding treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…The problem arises when unrealistic optimism clouds an individual's assessment of the possible risks and benefits, when hope impedes effective consent. Recent papers from Sulmasy8 and Jansen et al 9 have identified a number of motivating issues that bear on participants attitudes to trials: the prevalence of faith (in individual physicians or science in general, in the miraculous or in a particular deity); and differences in the way that dispositional and unrealistic optimism play out in the consent process.…”
mentioning
confidence: 99%